2020
DOI: 10.1093/braincomms/fcaa041
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal evaluation of the natural history of amyloid-β in plasma and brain

Abstract: Plasma amyloid-β peptide concentration has recently been shown to have high accuracy to predict amyloid-β plaque burden in the brain. These amyloid-β plasma markers will allow wider screening of the population and simplify and reduce screening costs for therapeutic trials in Alzheimer’s disease. The aim of this study was to determine how longitudinal changes in blood amyloid-β track with changes in brain amyloid-β. Australian Imaging, Biomarker and Lifestyle study participants with a minimum of two assessments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 21 publications
3
28
0
Order By: Relevance
“…We found significantly lower plasma Aβ42/Aβ40 in amyloid PET-positive CU study participants with two MS based (IP-MS:WashU and IP-MALDI-TOF-MS:Shimadzu) and two IA (IA:Quanterix and IA:Roche) platforms. These results corroborate findings from other studies that have reported lower plasma Aβ42/Aβ40 in PET-positive cognitively normal older adults using MS based (11) and IA assays (6). Compared to CSF, where Aβ42/Aβ40 ratio difference between PET-positive to negative could be up to 50% (25), the differences seen with the plasma levels are quite small (7-12%).…”
Section: Diagnostic Utility Of Plasma Aβ42/aβ40 For Amyloid Status De...supporting
confidence: 90%
See 1 more Smart Citation
“…We found significantly lower plasma Aβ42/Aβ40 in amyloid PET-positive CU study participants with two MS based (IP-MS:WashU and IP-MALDI-TOF-MS:Shimadzu) and two IA (IA:Quanterix and IA:Roche) platforms. These results corroborate findings from other studies that have reported lower plasma Aβ42/Aβ40 in PET-positive cognitively normal older adults using MS based (11) and IA assays (6). Compared to CSF, where Aβ42/Aβ40 ratio difference between PET-positive to negative could be up to 50% (25), the differences seen with the plasma levels are quite small (7-12%).…”
Section: Diagnostic Utility Of Plasma Aβ42/aβ40 For Amyloid Status De...supporting
confidence: 90%
“…Recent advancements in the biochemical assays of Aβ in blood-based biofluids (serum, plasma) via ultra-sensitive immunoassays (IA) and targeted massspectrometry (MS) have engendered remarkable Aβ blood tests with proven accuracy for detecting brain amyloid pathological status, as confirmed via PET or CSF (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16); discriminating AD from cognitive normal status (15), as well as predicting cognitive decline (6,17) and clinical progression (18); alluding to high potential for clinical use. Of the variations of amyloid protein, including precursors and independent Aβ isoform types investigated, plasma Aβ42/Aβ40 ratio has been shown to reliably predict abnormal cerebral amyloid deposition in non-demented older adults, with the MS based platforms shown to provide the most robust results of AUCs reported up to 0.88 (11,19) also in a recent multicohort head-to-head comparison of multiple platforms (8).…”
mentioning
confidence: 99%
“…We also explored levels of ApoE [90], ApoJ [91], inflammatory markers [92], and micro-RNA [93]. New A␤ immunoassays showed improved performances [94][95][96] but the combination of immunoprecipitation and mass spectrometry proved to have exceptional performance [97], equivalent to CSF assays. Notably, measurement of the natural history of plasma A␤ change, via one of the new immunoassays, suggests that the trajectory of plasma A␤ change mirrors brain A␤-amyloid accumulation as measured by PET, with a rapid phase of plasma change observable up to 6 years prior to the rapid phase of brain A␤-amyloid accumulation [96].…”
Section: Blood Biomarkers: Plasma Aβ/tau Lipidomics and Metabolomicsmentioning
confidence: 99%
“…New A␤ immunoassays showed improved performances [94][95][96] but the combination of immunoprecipitation and mass spectrometry proved to have exceptional performance [97], equivalent to CSF assays. Notably, measurement of the natural history of plasma A␤ change, via one of the new immunoassays, suggests that the trajectory of plasma A␤ change mirrors brain A␤-amyloid accumulation as measured by PET, with a rapid phase of plasma change observable up to 6 years prior to the rapid phase of brain A␤-amyloid accumulation [96]. CSF and plasma A␤ 42 are in equilibrium, and are expected to show changes earlier than A␤-PET since the dynamic range of CSF change is greatest at the lower ranges of A␤-PET.…”
Section: Blood Biomarkers: Plasma Aβ/tau Lipidomics and Metabolomicsmentioning
confidence: 99%
“…Within this context, quantitative models of disease progression, Disease progression Models referred to as DPMs, have been proposed (Fonteijn et al, 2012; Jedynak et al, 2012; Nader et al, 2020; Oxtoby et al, 2017; Schiratti et al, 2015), to quantify the dynamics of the changes affecting the brain during the whole disease span. These models rely on the statistical analysis of large datasets of different data modalities, such as clinical scores, or brain imaging measures derived from MRI, Amyloid-and Fluorodeoxyglucose-PET (Bilgel et al, 2015; Burnham et al, 2020; Donohue et al, 2014; Y Iturria-Medina et al, 2016; Koval et al, 2018). In general, DPMs estimate a long-term disease evolution from the joint analysis of multivariate time-series acquired on a short-term time-scale.…”
Section: Introductionmentioning
confidence: 99%